Progressive encephalomyelitis with rigidity and myoclonus (PERM). Issue 1 (28th July 2021) - Grech, Neil; Caruana Galizia, John Paul; Pace, Adrian
Abstract : Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a subtype of stiff-person syndrome (formerly stiff-man syndrome). It is rare and disabling, and characterised by brainstem symptoms, muscle stiffness, breathing issues and autonomic dysfunction. We describe a 65-year-old man who presented with odynophagia together with tongue and neck swelling, followed by multiple cranial nerve palsies culminating in bilateral vocal cord paralysis with acute stridor. He subsequently developed progressive generalised hypertonia and painful limb spasms. Serum antiglycine receptor antibody was strongly positive, but antiglutamic acid decarboxylase and other antibodies relating to stiff-person syndrome were negative. We diagnosed PERM and gave intravenous corticosteroids and immunoglobulins without benefit; however, following plasma exchange he has made a sustained improvement.